Economic value and determinants of effective household solid waste collection services in Kano, Nigeria - Basiru, Hamisu Alhaji (2017)
Solid waste management (SWM) in Kano metropolis is under the responsibility of urban authority, known as, Refuse Management and Sanitation Board (REMASAB). Waste management is a critical issue in the metropolis due to dwindling financial resources and population escalation. These problems result in poor control and handling SWM effectively and efficiently, giving rise to adverse threats on both environmental and public health. In a radical policy response to address this environmental problem, Kano State government proposed to privatize SWM services, via REMASAB, for improved collection services, as a better management option to ensure sustainability in SWM in Kano metropolis. Thus, the aim of this study is to estimate the economic values and determinants of waste collection services and their potentials towards effective waste management in Kano metropolis. Choice Experiment (CE) and Contingent Valuation Methods (CVM) valuation techniques were employed in the study. In the CVM section, willingness to pay (WTP) elicitation format, dichotomous choice and a close ended question were employed. In the CE part, five categories of non-market values of waste collection services were defined including: collection frequency, storage facilities, disposal method, pre-collection services and collection value. A total of 400 respondents were interviewed in face-to-face format, using cluster random sampling method. In the CVM section, logit model was defined based on dichotomous choice method for the estimation of the WTP off a specified bid amount to the hypothetical price for waste collection services. The logit model was used to drive marginal value and compensating surplus of the respondents to the attributes of non-market values of waste collection services.The results of mean WTP was estimated using single bounded dichotomous choice contingent valuation (DC-CVM) format, however, the result demonstrated respondents positive WTP for improve waste collection services. The estimated mean WTP was ₦2202.03 ($11.7) per household, and from the CE ₦2593.2 ($13.2) per household respectively. . The households’ statistics acquired from the 2006 Population Census data that Kano metropolis has a total number of 275,851 households. This implies an aggregate welfare gain worth ₦607, 432,177.53 ($3, 08,412.06) monthly, or ₦7, 289,186,130.4($33,000,944.82) annually, for the CVM and ₦715, 336813.2 ($3, 631151.3) monthly and annually ₦858,404, 1758, 4 ($43, 573816) for the CE. Invariably, this study generate significant information on the practical potentials for improving waste collection services in Kano metropolis. Generally, the results, in this research indicated that households placed high value on the collection services, and they are willing to pay for their waste collections in sustainable manner. These findings can be used for larger societal awareness about the waste collection services and the incurred benefits, including economic benefits. The results would also be beneficial to policy makers and PSPs to set priorities to ensure that the polluters’ pay principal is observed accordingly for environmental sustainability.